Serum Vitamin D in Children with Hemophilia A and Its Association with Joint Health and Quality of Life - Aida M. S. Salem; Takwa Mohamed AbdEltwwab; Hanan Hosni Moawad; Marwa O. Elgendy; Reham S. Al-Fakharany; Ahmed Khames; Mohamed Hussein Meabed (Hematology Reports, 2024)
Background/Objectives: Hemophilia A is an X-linked recessive illness produced by a deficiency of coagulation factor VIII. This study aimed to evaluate serum vitamin D in hemophilic pediatric patients and its correlation with joint health and quality of life. Methods: This case-control study was performed on ninety children under the age of 18 years old and separated into two groups: study group of 45 children with hemophilia A and control group of 45 healthy children at an outpatient pediatric hematology clinic at the Beni-Suef University hospitals. Results: Serum vitamin D levels were significantly lower in hemophilia A patients than in controls (p < 0.001). The level of serum vitamin D was deficient in 38 (84.4%), insufficient in 4 (8.8%) and sufficient in 3 (6.6%) in the study group while deficient in 8 (17.7%), insufficient in 16 (35.5%) and sufficient in 21 (46.6%) in the control group. Total hemophilia joint health score (HJHS) had a significant negative correlation with serum total calcium (R = −0.31, p = 0.038) and serum vitamin D level (R = −0.974, p < 0.001) while also positively correlated with alkaline phosphatase (R = 0.834, p < 0.001). A quality-of-life index that is specific to total hemophilia (Haemo-Qol/Haem-A-QoL) had a significant positive correlation with total hemophilia joint health score (HJHS) (R = 0.934, p < 0.001) and negatively correlated with serum vitamin D level (R = −0.924, p-value lower than 0.001), alkaline phosphatase (R = 0.842, p < 0.001), and severity of hemophilia (R = 0.67, p < 0.001). Conclusions: patients with hemophilia A had lower vitamin D levels than healthy controls. The severity of vitamin D deficiency is related positively to (HJHS) hemophilia and quality of life hemophilia cases according to Haemo-QoL.